EFFECT OF HARVESTING AGE ON THE MACRO AND MICRO MINERALS COMPOSITION OF CONGO GRASS, MULATO II AND GUINEA GRASS - Dandara G.B.; Aganga, A. A.; Ekeocha A. H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The experiment was carried out at the Department of Crop Science and Horticulture, Teaching and Research Farm, Federal University Oye Ekiti to determine the effect of harvesting age on the macro and micro minerals concentration of Congo grass, Mulato II and Guinea grass. The experimental site was cleared and demarcated with pegs into 32 plots. Each plot was 4m in length and 4m in (16m2). Brachiaria ruziziensis, Brachiaria Mulato II and Panicum maximum seeds were sown directly in the experimental plots with 30cm intra-row spacing and 60cm inter-row spacing with each plot replicated (4) times in a Randomized Complete Block Design (RCBD). The result showed that sodium, calcium and potassium were significantly (P<0.05) higher at week 4 post germination in Mulato II (91.6ppm, 185.87ppm and 350ppm respectively) and lowest in Congo grass. These values decreased as Mulato II matures to 78.60ppm, 160.67ppm and 306.33ppm for sodium, calcium and potassium respectively. The calcium, sodium and potassium contents of Mulato II were significantly (P<0.05) higher at weeks 4, 6, 8 and 10 post germination than in Congo and Guinea grasses. Copper and Iron were significantly (P<0.05) highest in Mulato II at weeks 4, 6, 8 and 10 post germination and lower in Congo and Guinea grasses. Copper and iron were 0.58ppm and 3.17ppm in Mulato II. Copper (0.58ppm) was significantly higher in Mulato II at week 4 and increased to 0.59ppm at week 10. Mulato II had significantly higher sodium, calcium, potassium and sulfur concentrations at all the harvesting ages than Congo and Guinea grasses. Harvesting age significantly affected macro minerals concentration in Congo, Mulato II and Guinea grasses. Harvesting at early stages is recommended to maximize mineral content for optimal livestock nutrition.